Responsibility of citizens in food safety social co-governance in the context of China - Wu, Linhai; Qin, Ke; Chen, Xiujuan (Frontiers in Public Health, 2022)
In the context of China’s current circumstances, this study identified all actors that hold some responsibility for ensuring food safety based on the complete food supply chain. Moreover, these actors’ responsibilities for ensuring food safety in the food safety social co-governance system were assessed using best–worst scaling and a mixed logit model from the perspective of citizen responsibility. The results demonstrated that, in descending order, responsibility for ensuring food safety goes from food producers and traders (including producers, distributors, and retailers) to the government, social organizations, news media, and finally to citizens. Food producers and traders are the actors who should take the greatest responsibility, whereas citizens bear the least responsibility. The study argues that, on the one hand, the responsibility of citizens in food safety co-governance should be recognized, but on the other hand, it should not be arbitrarily extended. In the future, based on the unique function of citizens in the social co-governance system, more diversified channels should be designed at the institutional level to allow citizens to participate in the supervision of food safety in production and marketing, discuss government food safety policies, and develop scientific literacy regarding food safety so that citizens are willing and able to participate in food safety co-governance.